2013
DOI: 10.1007/s10266-013-0125-2
|View full text |Cite
|
Sign up to set email alerts
|

Differential efficacy of endodontic obturation procedures: an ex vivo study

Abstract: By means of a double-chamber model, different root canal filling materials and procedures were compared. Briefly, the root canals of single-rooted human teeth, extracted for periodontal reasons, were instrumented and obturated by gutta-percha/Pulp Canal Sealer EWT (PCS) or by Resilon, in association with different sealers (Real Seal, RelyX Unicem or Meta). Obturation was achieved by traditional continuous wave of condensation technique (TCWCT), a modified version of it (MCWCT), or single cone technique (SCT). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
0
6
0
4
Order By: Relevance
“…); otherwise, infiltration of tissue fluids could provide a substrate for bacterial growth (Siqueira , Ardizzoni et al . ). A possible way of improving the bactericidal efficacy of disinfecting solutions is to incorporate detergents as surface‐active agents to enhance their wetting properties (Glantz & Hansson , Giardino et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…); otherwise, infiltration of tissue fluids could provide a substrate for bacterial growth (Siqueira , Ardizzoni et al . ). A possible way of improving the bactericidal efficacy of disinfecting solutions is to incorporate detergents as surface‐active agents to enhance their wetting properties (Glantz & Hansson , Giardino et al .…”
Section: Introductionmentioning
confidence: 97%
“…Increasing the concentration of NaOCl from 1% to 6% improved the penetration depth of its antibacterial action, but complete eradication of bacteria from dentinal tubules could not be achieved, especially beyond the first 300 lm from the pulp-dentine junction (Wong & Cheung 2014). Therefore, remaining bacteria should be entombed by root fillings (Peters et al 1995); otherwise, infiltration of tissue fluids could provide a substrate for bacterial growth (Siqueira 2001, Ardizzoni et al 2014. A possible way of improving the bactericidal efficacy of disinfecting solutions is to incorporate detergents as surface-active agents to enhance their wetting properties (Glantz & Hansson 1972.…”
Section: Introductionmentioning
confidence: 99%
“…The tridimensional root filling could prevent coronal infection or re-infection [2,3]. However, root canal fillings are affected by gaps that alter their sealing ability [4]. Gaps may be connected and may create a sort of complex spiral network that affects the tridimensional morphology of the root filling [5].…”
Section: Introductionmentioning
confidence: 99%
“…Several in vitro studies have reported bond strength values of different adhesive systems used in combination with a luting composite to both enamel and dentin 16,17,18,19,20. In view of these desirable features, this material could be used as an endodontic sealer.…”
Section: Introductionmentioning
confidence: 99%
“…In view of these desirable features, this material could be used as an endodontic sealer. A recent study demonstrated good results when associating RelyX Unicem to Resilon cones 20. However, up to the present date, little information regarding its potential to be used as an endodontic sealer is available in the literature.…”
Section: Introductionmentioning
confidence: 99%